Anorexia nervosa: A phenomenological exploration of family life. - Emmrys, Charles. (University of Ottawa (Canada), 1993)
The current study consists of a phenomenological exploration of the family life of an adolescent diagnosed as suffering from anorexia nervosa. A review of the literature addressing the anorectic's family life revealed that the various theoretical formulations offered were not well validated by experiential data collected from those living in the family. The theoretical orientations of the various authors also appeared to prestructure the accounts. Questions were thus raised regarding the inherent validity of these formulations which lead to more general questions concerning the epistemological and philosophical grounding on which a study of family life should be based. In a second section, the issue of the most appropriate philosophical grounding for a study of family life was addressed. Of the epistemological philosophical positions reviewed, the one which revealed itself to present the most primary and irrefutable grounding for a pursuit of psychological research in general and family research in particular was the existential phenomenological ontological approach. A methodology consistent with the Duquesne School's approach to psychological research was adapted for the study. The results of the study revealed that family life prior to the onset of anorectic symptoms was well structured in terms of division of authority and responsibilities. The approach to family living, however was very much centered in the home with the most important relationships in each member's life being usually contained within the family. Particularly important were the cross-generational relationships which, for the children, were important forums for addressing developmental and autonomy issues. The anorectic was the child most involved in these relationships. The onset of symptoms coincided with a crisis of authenticity experienced by the anorectic which led to an attempt at self-isolation and reduced investment in the family. The anorectic dieting behavior was described as being part of a project of self-definition and renewal. The impact of the withdrawal on the family was to transform it into a conflicted environment which corresponded to many of the descriptions provided by previous authors. The hospitalization helped defuse the intrafamilial conflict but failed to address the core issue of the anorectic's quest for authenticity.
Keywords: Psychology, Developmental.